Theory of the firm for strategic management : economic value analysis - Becerra, Manuel, 1964- (Cambridge, UK ; New York : Cambridge University Press, 2009)
Strategic decisions deal with the long-term direction of the firm and its main activities, usually the responsibility of the top managers in an organization. Because the firm is the critical unit of analysis in strategy, we need to define what firms are, how they create value, and what their organizational boundaries are in order to understand their overall performance. However, this must be done in a manner that is most useful for strategic analysis and decision making. In other words, we need a theory of the firm for business strategy. Theory of the Firm for Strategic Management integrates and expands key existing theories, like transaction costs economics and the resource-based view, to develop a value-based theory of the firm. This provides a framework to show how firms can create value for customers and, at the same time, capture economic profits for their owners through business, corporate, international, and social strategies.
Introduction -- The contracting view of the firm -- The nature of the firm in strategy -- Creating economic value -- The appropriation of value by firms -- Business strategy -- Corporate strategy -- International strategy -- Strategy and social value -- Value analysis in strategy.
Includes bibliographical references and index.
Print version record.
Added to collection customer.56279.3
Keywords: Strategic planning; Management; Business enterprises; Planification stratégique.; Gestion; Entreprises; management; BUSINESS & ECONOMICS -- Strategic Planning; Business enterprises; Management; Strategic planning; Strategisches Management; Unternehmen; Strategische planning